PEMBERDAYAAN PEREKONOMIAN MASYARAKAT MELALUI PENDEKATAN ONE VILLAGE ONE PRODUCT PADA KOPERASI TANI MERTANADI DI DESA PELAGA, KECAMATAN PETANG, KABUPATEN BADUNG (CITIZEN CHARTER, 2022)
Koperasi Tani Mertanadi is a cooperative business that is engaged in asparagus production through the OVOP approach in empowering the economy of rural communities . But in its implementation there are problems such as breeding, mentoring and the marketing process. The method used in this research is descriptive qualitative. Based on the study, this research uses the theory of community empowerment according to Mardi Yatmo Hutomo. The results of the study show that several indicators have been running well such as indicators of capital assistance, infrastructure development assistance, assistance assistance, institutional strengthening and strengthening partnerships, but not yet optimal due to several obstacles such as indicators of infrastructure development, then indicators of strengthening partnerships and on the indicators of mentoring is quite good but needs to be improved again, especially assistance on cooperative operational management. Keywords: Community Empowerment, OVOP Approach, Cooperative